The New Science of Fighting Silent Heart Disease: Causes, Diagnoses, Prevention, and Treatments - Karpman, Harold L. (Rowman & Littlefield Publishers, 2020)
On average, 50% of all heart attacks are silent – that is, they are painless and leave behind damage that remains undetected – unless the patient and his or her doctor are looking for it. Silent heart disease is a significant cause of sudden death – American’s number one public health problem with more than 600,000 sudden deaths and 1.5 million heart attacks occurring in the U.S. each year. This book tells you everything you need to know in the order to detect and treat this silent killer. Written by a celebrated cardiologist who has successfully treated thousands of patients in his career spanning 50 years, it offers practical advice for all readers and provides insight into a type of asymptomatic cardiac condition that affects almost half of all those afflicted with heart disease.